FORMULASI KRIM EKSTRAK ETANOL DAUN LAMUN (Syringodium isoetifolium) - Juwita, Anisa Puspa; Yamlean, Paulina V.Y; Edy, Hosea Jaya (UNIVERSITAS SAM RATULANGI, 2013)
Seagrass (Syringodium isoetifolium) is a plant that lives submerged at sea, this floweringplant, leaves, and stems that are plugged into a powerful in water. The chemical content ofthe leaves of the Seagrass is a flavonoid, phenol, hydroquinone, and antioxidants.This studyaims to determine the quality of the cream of seagrass leaf extracts using a concentration of5%, 10%, 20% dan 40%. on organoleptic testing conducted cream, homogeneity test, testdispersive power, pH and absorbance test. results obtained in the organoleptic seen from thecolor green, semi-solid dosage forms and distinctive smell seagrass cream. homogeneity test.homogeneity test cream seagrass leaf extract with a concentration of 5% 10% 20% and 40%did not experience any clumping or phase separation dispersive power test creams rangedfrom 2.5 cm - 3.5 cm. pH ranged from 4.93 - 5.96 and test absorption ranged from 3.7 ml - 5ml. seagrass leaf extract cream with type W/O creams that meet the test of homogeneity testquality, dispersive power test, test and test pH absorptionKeyword : Syringodium isoetifolium, Seagrass Leaves, Cream W/O